SiDREB2-based SNAP Marker-Assisted and Multi-Trait Selection in The Early Generation of Foxtail Millet (Setaria italica L. Beauv.) - Butarbutar, Lidya Kristina Sari; Syawaluddin, Dwi Dana; Suwarno, Willy Bayuardi; Ardie, Sintho Wahyuning (Universitas Gadjah Mada, 2024)
Setaria italica L. or foxtail millet is known for its nutritious grains and adaptability to unfavorable environmental conditions. High productivity, early heading, medium stature, and tolerance to drought- or salinity stress are among the breeding objectives for foxtail millet. The objective of this study was to select F3 families of foxtail millet from the cross of Botok-10xICERI-6 by weighted selection index and assisted by SiDREB2-based SNAP marker. Genotyping of 178 F3 families using the SiDREB2-based SNAP marker resulted in 29 A/A genotypes, 121 A/G genotypes, and 28 G/G genotypes. Further evaluation was conducted on 48 F3 families consisting of 27 A/A genotypes and 21 A/G genotypes in an augmented randomized complete block design together with their parental genotypes (Botok-10xICERI-6) and three check genotypes (Mauliru-2, NTB-1, and Toraja). Plant height and heading time had high broad-sense heritability, whereas grain weight per plant had a moderate broad-sense heritability. Ten potential F3 families were selected based on a weighted selection index with 20% intensity, comprised of seven A/G genotypes and three A/A genotypes with a weighted selection index ranging from 0.84 to 3.76. The F3 family with pedigree numbers B10I6-15-136, B10I6-15-161, and B10I6-15-70 with A/A genotypes are considered putative transgressive segregants and could be continued to the next generation for further breeding process.